Respuesta :

Step-by-step explanation:

so, it is a quadratic equation :

-3x² + 30x - 90 = 0

the first thing we can do is divide by 3

-x² + 10x - 30 = 0

remember, the formula to solve and find the 2 solutions is

x = (-b ± sqrt(b² - 4ac))/(2a)

in our case here

a = -1

b = 10

c = -30

x = (-10 ± sqrt(100 - 4×-1×-30))/-2 =

= (-10 ± sqrt(100 - 120))/-2 = (-10 ± sqrt(-20))/-2 =

= (-10 ± sqrt(4×5)i)/-2 = (-10 ± 2×sqrt(5)i)/-2 =

= 5 ± -sqrt(5)i

x1 = 5 - sqrt(5)i

x2 = 5 + sqrt(5)i

remember, i = sqrt(-1), a complex number.